2005
DOI: 10.1021/la050554l
|View full text |Cite
|
Sign up to set email alerts
|

Unified Concept of Solubilization in Water by Hydrotropes and Cosolvents

Abstract: In the present work hydrophobic dyes, i.e. disperse red 13 (DR-13; (2-[4-(2-chloro-4-nitrophenylazo)-N-ethylphenylamino]ethanol) and Jaune au gras W1201 (1H-indene-1,3(2H)-dione,2-(2-quinolinyl)), are solubilized in water with the help of different additives: acetone and 1-propanol as typical cosolvents, sodium xylene sulfonate (SXS) as a representative of a classical hydrotrope, sodium dodecyl sulfate (SDS) as a typical surfactant, and finally some "solvosurfactants" [ propylene glycol monoalkyl ether derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(160 citation statements)
references
References 22 publications
11
147
0
1
Order By: Relevance
“…The latter belongs to a class of molecules generally called hydrotropes, that are defined as small amphiphilic molecules that do not form well defined micelles in water. 13 The least efficient electrolytes are the metallacarboranes and DBSA, which appear at the same region in the I/V plot through the whole range of applied voltages. Although the molecular structure of [1] -does not display the conventional structure of a surfactant, in this work we provide the results of a macroscopic experiment proving the surfactant behaviour in aqueous solutions of [1] -and that this is due to the formation of aggregates.…”
Section: Resultsmentioning
confidence: 97%
“…The latter belongs to a class of molecules generally called hydrotropes, that are defined as small amphiphilic molecules that do not form well defined micelles in water. 13 The least efficient electrolytes are the metallacarboranes and DBSA, which appear at the same region in the I/V plot through the whole range of applied voltages. Although the molecular structure of [1] -does not display the conventional structure of a surfactant, in this work we provide the results of a macroscopic experiment proving the surfactant behaviour in aqueous solutions of [1] -and that this is due to the formation of aggregates.…”
Section: Resultsmentioning
confidence: 97%
“…PVA/borax hydrogels, on the other hand, show mechanical features suitable for easy removal by peeling from surfaces, without need of strong mechanical or chemical actions, and have been therefore proposed for cleaning purposes [14,[18][19][20]. Water/ cosolvent mixtures can be embedded into these high viscosity polymeric dispersions, making them able to soften and swell water-insoluble materials, in a way similar to that proposed in a study concerning the solubilization of hydrophobic substances by hydrotropes in water [21].…”
Section: Introductionmentioning
confidence: 93%
“…The compositions used for these experiments are Bauduin et al showed a way to characterize the hydrophobic efficiency a. 36 It is linked to the evaluation of the slopes of the linear part in the log-linear plots of the solubility of the hydrophobic dye, which is defined using the following equation:…”
Section: Solubilisation Experimentsmentioning
confidence: 99%